2013
DOI: 10.1016/j.jvir.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Percutaneous Interventions for Hepatic Venous Outflow Obstruction after Pediatric Living Donor Liver Transplantation: Experience from a Single Institute

Abstract: Percutaneous interventions were effective treatments for HVOO after LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 22 publications
4
52
1
Order By: Relevance
“…Some authors have suggested that a second angioplasty procedure is required when recurrence ensues after a first balloon angioplasty procedure, with stenting being considered appropriate for cases that recur despite a second angioplasty procedure. 8,10,13 In one study, satisfactory results were attained with repeat angioplasty, with no cases of subsequent rupture, thrombosis, or mortality. 13 Thus, repeat angioplasty could be a safe treatment option.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors have suggested that a second angioplasty procedure is required when recurrence ensues after a first balloon angioplasty procedure, with stenting being considered appropriate for cases that recur despite a second angioplasty procedure. 8,10,13 In one study, satisfactory results were attained with repeat angioplasty, with no cases of subsequent rupture, thrombosis, or mortality. 13 Thus, repeat angioplasty could be a safe treatment option.…”
Section: Discussionmentioning
confidence: 97%
“…There is no consensus in the literature as to which of the options of balloon angioplasty, balloon angioplasty plus stenting, or primary stenting should be selected for treatment of early-onset HVOO cases. 6,10 Although authors have reported favorable outcomes with primary stenting, they have also advocated that balloon angioplasty is still the best option for early-onset HVOO, suggesting that stents both increase the tendency for thrombosis and cause technical difficulties in the case of repeated liver transplant. 3 In contrast, the rationale of authors advocating avoidance of balloon angioplasty are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…In our reported study [14] , the rates of technical success, primary patency and primary-assisted patency were evaluated. Technical success is defined as success in interventional procedures.…”
Section: Resultsmentioning
confidence: 99%
“…[13] A venogram is performed and the pressure gradient is measured to confirm the diagnosis, usually via a transjugular or transfemoral route (Fig. 5).…”
Section: Hepatic Vein Stenosismentioning
confidence: 99%